Depressão e sofrimento emocional durante a gravidez e separação dos filhos em mulheres encarceradas no Estabelecimento Prisional Feminino de Viana em Luanda, Angola - Catito, Filomena Graciano Lamberga (2015)
This research is a qualitative and quantitative study based on the Winnicottian psychoanalytic theory, aiming to understand the experience of imprisoned women in relation to: different ways to face prison life, pregnancy, breastfeeding, calving, children upbringing, separation after three years, continuity of this relationship after separation and observation of depression signs. Twenty women participated in the survey, ranging from 18 to 41 years of age, of which ten were pregnant or ten were imprisoned with their children. Two instruments were used for data production: the semi-structured interview and the Beck depression test (BDI-II). We sought to understand the grief of these women caused by prison during and after pregnancy, the time of separation from their children and the high depression rate within this population. Analysis of the results indicated that incarceration causes suffering, pain, anger, sadness, humiliation and a high rate of serious depression in pregnant women and those who live with their children in prison, feeling powerless and dependent upon the prison, and that the separation from their children leaves them in shock due to the uncertainty of a good continuance in the children‟s care, in addition to the fear of being forgotten by them. Family support is a key factor in the lives of these women, as family abandonment increases their suffering. Having a partner was also a prime factor that brought them respect towards other inmates, thus increasing their self-esteem. All the women stated that the prison environment is maddening, full of falsehood and hypocrisy, and the best way to handle the situation is remaining isolated, obeying orders and not speaking about other people‟s lives